Bauhaus Courses at the Rippl-Rónai Art Institute - Appelshoffer, Péter; Ficzek, Ferenc; Gimesi, Judit; Gyenes, Zsolt; Jónás, Péter; Károly, Sándor Áron; Mátis, Rita; Molnár, Ágnes Éva; Szabó, Zsófia; Szalay, Miklós; Szigethy, Anna (ARTCADIA, 2022)
In the spring semester of the 2018/2019 academic year, the Rippl-Rónai Art Institute’s teachers designed student projects in the spirit of the Bauhaus centenary. This experiment was an attempt to revive the Bauhaus methods through a fresh, contemporary approach. As paraphrases, reflections and reinterpretations of the Bauhaus style, the students’ works were produced in different genres, technical backgrounds and media (paintings, graphics, animations, films, installations, performances, prints, etc.). This text, edited in catalogue format, is an illustrated documentation of the projects: teachers’ reports on the specific tasks of each course, the work processes and the experiences.